Transformasi Lingkungan: Inisiatif Bank Sampah Ngudi Lestari di Kelurahan Tinjomoyo, Kota Semarang - Davin Yusuf Nasrullah; Muhammad Rafli Al Hafidz; Faqih Ilhamsyah; Devina Meisyarani; Hilyatul Karimah Azzahra; Leni Khasanatul Farikhah; Ajeng Putri Salokha; Nailah Mardhiyah; Fuji Astutik (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
The Ngudi Lestari Waste Bank program, located in Tinjomoyo Village, Banyumanik Subdistrict, Semarang City, is an innovative effort to address the increasingly pressing waste problem in urban environments. This waste bank serves as a center for waste collection, sorting, and processing, transforming waste into economically valuable resources and educating the community on the importance of recycling and waste management.This research used a qualitative approach with a case study method to evaluate the Ngudi Lestari Waste Bank initiative. Data were collected through observation, interviews, and documentation, then analyzed using triangulation techniques. The results indicate that Ngudi Lestari Waste Bank is effective in raising environmental awareness, changing community behavior patterns, and strengthening social solidarity. Support from the government is crucial in expanding and optimizing the program's impact. With various future development plans, this initiative is expected to become a sustainable waste management model and be adopted by other regions, as well as a concrete example for waste management solutions at the local level.